Does Functional Somatic Symptoms Measurement Differ Across Sex and Age? Differential Item Functioning in Somatic Symptoms Measured With the CIDI. (October 2022) - Acevedo-Mesa, Angélica; Monden, Rei; Castro-Alvarez, Sebastian; Rosmalen, Judith G. M.; Roest, Annelieke M.; Tendeiro, Jorge N.
Functional Somatic Symptoms (FSS) are physical symptoms that cannot be attributed to underlying pathology. Their severity is often measured with sum scores on questionnaires; however, this may not adequately reflect FSS severity in subgroups of patients. We aimed to identify the items of the somatization section of the Composite International Diagnostic Interview that best discriminate FSS severity levels, and to assess their functioning in sex and age subgroups. We applied the two-parameter logistic model to 19 items in a population-representative cohort of 962 participants. Subsequently, we examined differential item functioning (DIF). "Localized (muscle) weakness" was the most discriminative item of FSS severity. "Abdominal pain" consistently showed DIF by sex, with males reporting it at higher FSS severity. There was no consistent DIF by age, however, "Joint pain" showed poor discrimination of FSS severity in older adults. These findings could be helpful for the development of better assessment instruments for FSS, which can improve both future research and clinical care.